Study on 10 GHz electromagnetic wave absorption of cullet doped with iron (II, III) oxide - Mansor, M.F.C. (Institute of Electrical and Electronics Engineers Inc., 2015)
Glass bottle waste was recycled into cullet to doped with iron (II, III) oxide, Fe3O4 have been found to possess a significant propensity for absorbing electromagnetic (EM) waves. In this work, the electromagnetic wave absorption composites, consisting of cullet and Fe3O4, were prepared by sintering a mixture of cullet raw material and iron (II, III) oxide powder. Reflection coefficient (S11) and transmission coefficient (S21) was measured at 10 GHz electromagnetic waves for the different percentage weight (wt) of cullet doped with Fe3O4. The absorption coefficient of electromagnetic wave was calculated based on the S11 and S21 measurement. The sample of cullet doped with Fe3O4 has a higher electromagnetic wave absorption comparable to the pure cullet raw material. Electromagnetic wave absorption performances of specimens can be controlled by changing the ratio between iron (II, III) oxide powder and cullet. Â© 2015 IEEE.